The Activities of the Lithuanian Diplomatic Corps in Europe during World War II - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2000)
The article examines the situation of the Lithuanian diplomatic service (LDS) during the Second World War and discusses the meetings of Lithuanian diplomats in Switzerland in 1941–1942. The aim of this article is to give an idea about the aspects of the LDS’s activities in Europe during the Second World War and to review two documents to which almost no reference is made in Lithuanian historiography.
Keywords: Soviet occupation; emigree; diplomacy; Second World War; Switzerland